The Suppressive Effect of Novel Hydrazones-Tethered Imidazoles in HCT-116 and HT-29 Colorectal Cancer Cells: Synthesis, Biological Activity and Molecular Modeling Studies - Kekecmuhammed, Huseyin; Tapera, Michael; Sahin, Kader; Sever, Beyza Ozturk; Anber, Anber M.; Bora, Rifat Emin; Avsar, Timucin (Wiley-V C H Verlag Gmbh, 2024)
A series of hybrid compounds containing both the imidazole ring and the hydrazone moiety have been synthesized. Synthesized compounds were characterized by various spectral techniques, including FT-IR, 1H-NMR, 13C-NMR, and HRMS. The compounds were evaluated for their antiproliferative activities on colorectal cancer cells HCT-116 and HT-29 in a time-dependent manner. Among them, some compounds exhibited remarkable anti-cancer activity with a less cytotoxic effect on non-cancerous cell lines, especially HRK-2 with IC50 value of 1.35 +/- 0.18 mu M in HCT-116 cells and HRK-5 with IC50 value of 2.67 +/- 0.61 mu M in HT-29 cells. Investigations of colon cancer cell death were performed, and the most active compounds were found to trigger cell death via nuclear localization and induce S phase arrest of the colon cancer cell. Moreover, molecular modeling studies for the synthesized compounds was performed to predict their binding affinities toward the active site of BCL-2. The findings of the molecular modeling investigations were highly consistent with those of the cytotoxicity results. A set of hydrazone-tethered imidazoles was synthesized by a three-component Bignelli-like reaction. Synthesized compounds were evaluated as anti-colon cancer agents, and their binding mechanisms were investigated. image
Keywords: Imidazole; Hydrazone; Colon cancer; Apoptosis; and Molecular modeling